Risk Analysis in Professional Terms and Insurance Tariff Algorithm - Tsintsadze, Asie; Gogoberidze, Tamar (European Journal of Sustainable Development, 2019)
Modern society has to live and have activities with risks daily. Consequently, the probability of adverse events is high. In the article, the objective of the research is the risks of professional liability, which, in contrast to other risks, damage the third person. In this kind of insurance, it is difficult to define the amount of damage, the amount of compensation. Therefore, Based on historical facts, an algorithm is designed to determine the professional liability insurance tariff, taking into account the principles of tariff policy and working out the professional rating scale. Keywords: professional Risk, Level of professionalism, Risk of insurance, Net rate, Insurance tariff, risk added